Correlation of Serum Dynorphin /KOR System with Serum IL-6 and IL-10 in Major Depressive Disorder - Hussein Kadhem Al-Hakeim (Journal of Global Pharma Technology, 2019)
A case-control study was applied to improve if there is a relation between endogenous opioid dynorhpin (Dyn) and its receptor KOR with serum interleukin-6 (IL-6) and interleukin-10 (IL-10) among MDD patients versus a group of apparently healthy subjects. The study included 60 depressed pretreatment male patients and 30 (age and gender matched) controls. The serum Dyn, KOR, IL-6 and IL-10 levels were measured and the relation between these factors was obtained in addition to comparison of these factors between MDD patients and control group. Each parameter was determined by using ELISA technique. The comparison between both groups indicated a significance increase (p<0.05) in Dyn, IL-6 and IL-10 in MDD group comparing with controls. Whereas KOR didn’t show any significant difference. The correlation results indicated that there was no correlation between the two systems (endogenous opioid and immune systems). The conclusion of the study is that there was no relation between Dyn/KOR with inflammatory marker IL-6 and IL-10. This finding indicates that there is no effect of endogenous dyn on the immune function.